The Multifaceted Landscape of Healthcare-Associated Infections Caused by Carbapenem-Resistant Acinetobacter baumannii - Alessandro Russo; Francesca Serapide (Microorganisms)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is an emerging and important major cause of nosocomial infections, posing a significant challenge to clinicians worldwide. The intrinsic and acquired resistance mechanisms exhibited by CRAB, associated with its ability to persist in healthcare environments, have transformed it into a critical public health concern. The clinical implications of CRAB infections include severe manifestations, like ventilator-associated pneumonia and bloodstream infections. These infections are often associated with increased morbidity and mortality, particularly in critically ill patients, such as those in intensive care units, immunocompromised, and those undergoing invasive procedures. Considering these characteristics, the therapeutic armamentarium for the treatment of CRAB infections is increasingly limited, as these strains exhibit resistance to a broad range of antibiotics, including carbapenems and the new β-lactam inhibitors, which are considered last-line agents for many bacterial infections. An important role is represented by cefiderocol and data from real-world evidence. The aim of this narrative review is to discuss the main topics of CRAB infection and strategies for prevention, management, and therapy.